Social Personalism, Its Implications for Education and Implementation in Society - Sławomir Chrost (Paedagogia Christiana, 2025)
The human-person is, according to personalism, open to others, needs others and creates various forms of community. The socialization of the human-person is, most of all, the outcome of lack and excess. The human-person, colloquially speaking, needs other people to grow, and needs interpersonal relationships to ‘give and take.’ The purpose of this essay is to outline the theoretical underpinnings of social personalism, its implications for pedagogy and selected examples of how it is cultivated in practice. The author demonstrates that the ‘I’ directed to the ‘you’ also becomes the ‘I’ for the ‘you.’ Thus, the theory of the human being – the person – as a relational being translates into the teleology of education and pedagogical practice. ‘I’ is oriented ‘towards’ and ‘for’ ‘you’/‘You,’ being ‘with’ ‘you’/‘You.’ It is worth noting that social personalism is a path ‘between’ individualism and collectivism. It attempts to combine the individual good with the common good through the characteristic of participation in the community. The pedagogy of the person comes to fruition in the community, according to the principles of companionship through dialogue. It strives for the full development of the human being as a person – a development that materialises through active love towards the other in a spirit of solidarity.